Trade and Investment Interactions in the Asia-Pacific Region: Long-Term Effects of Sanctions - Dmitriy Aleksandrovich Izotov (Prostranstvennaâ Èkonomika, 2025)
The Asia-Pacific region (APR) is the largest sub-global economy, accounting for a large share of global trade and direct investment flows, where the major role is played by intraregional economic interactions. The expansion of trade and investment in the APR has been hampered by sanctions, the number of which has increased significantly over the past decade. The aim of this study is to assess the long-term cumulative effects of sanctions on trade and investment interactions between the APR countries in 1992–2023. The study examined trade sanctions, financial sanctions, travel sanctions, arms sanctions, military aid sanctions, and other sanctions reflected in the Global Sanctions Data Base (GSDB). Based on the estimates obtained, it was found that sanctions generally restrained the exchange of goods (by 31.5%) and capital (by 34.3%) between the APR countries. The negative effect of specific types of sanctions that were geopolitically oriented was the most significant in reducing trade between opposing countries: other sanctions – by 77.2%, arms sanctions – by 50.9%, military aid sanctions – by 46.4%. On average, trade sanctions reduced trade by 28.4% over the period, while the impact of other types of sanctions on trade in the APR was statistically insignificant. The following types of sanctions had a negative impact on foreign direct investment (FDI) inflows: travel sanctions – by 91.6%, other sanctions – by 83.9%, and financial sanctions – by 54.5%. The remaining sanctions did not have a significant impact on capital inflows in the Asia-Pacific region. The calculations showed that the effect of globalization generally offset the impact of sanctions on trade between Asia-Pacific countries, but depended on the specific type of restrictions. In turn, the effect of globalization did not have a significant impact on mitigating the negative impact of sanctions on FDI inflows to the APR countries. This circumstance indicates that, unlike trade, FDI inflows to the APR countries were much more vulnerable to sanctions. This significantly narrows the opportunities for sanctioned countries to attract direct capital, which can be replaced by responsible investments through net exports